2002
DOI: 10.1590/s0021-75572002000100015
|View full text |Cite
|
Sign up to set email alerts
|

Deficiência auditiva neurossensorial associada à doença de Kawasaki

Abstract: ResumoObjetivo: a doença de Kawasaki (DK) é uma vasculite sistêmi-ca idiopática, autolimitada, de pequenos e médios vasos. Foram descritos na literatura treze casos de deficiência auditiva neurossensorial, durante a evolução dessa doença. Descreve-se o caso de um lactente com doença de Kawasaki com evolução, durante a fase aguda, para deficiência auditiva neurossensorial. A descrição do caso justifica-se por ilustrar uma complicação grave da DK, pouco mencionada na literatura, que reforça a recomendação de cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
(14 reference statements)
0
3
0
4
Order By: Relevance
“…During the acute phase, various organs including the heart are affected, showing diverse symptoms. In particular, the incidence of central nerve system involvement in Kawasaki disease ranges from 1.1% 16 17) to 30% 4 18) , showing as aseptic meningitis, seizure, ataxia, transient facial paralysis, sensorineural hearing loss, and subdural effusion 10) . Although sensorineural hearing loss can cause serious problems in the language development period, the etiological and clinical manifestations are still not fully described, and insufficient attention has been paid to them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the acute phase, various organs including the heart are affected, showing diverse symptoms. In particular, the incidence of central nerve system involvement in Kawasaki disease ranges from 1.1% 16 17) to 30% 4 18) , showing as aseptic meningitis, seizure, ataxia, transient facial paralysis, sensorineural hearing loss, and subdural effusion 10) . Although sensorineural hearing loss can cause serious problems in the language development period, the etiological and clinical manifestations are still not fully described, and insufficient attention has been paid to them.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, studies on the association have been conducted, but interpretations of the outcomes have varied 20) . Novo et al 5) , Clausen et al 11) , and Silva et al 18) reported cases of profound bilateral sensorineural hearing loss in patients with Kawasaki disease, despite the use of steroids for treatment, their hearing function was not improved. They reported that the sensorineural hearing loss might be caused by acute inflammatory reaction in the blood vessels of the middle ear, and their clinical manifestations were not same as those caused by aspirin ototoxicity 5 18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Objetivo Tipo População P1 14 Ilustrar uma complicação grave da DK. Estudo de caso Menino de um ano e sete meses com diagnóstico de DK.…”
Section: Publicação (P)unclassified
“…Percebe-se, ao mesmo tempo, que tem uma apresentação clínica comum com outras doenças infecciosas febris que são predominantes na infância, dificultando ainda mais o seu diagnóstico. 14 Apresenta-se a DK atípica com sintomas incomuns da DK incompleta, sendo fundamental diferir a segunda, que apresenta sintomas clássicos, da primeira, que se caracteriza pelo aumento do fígado, perda auditiva neurossensorial e icterícia. 30 Podem-se observar quanto às pautas interventivas dos enfermeiros relatadas nos estudos: o auxílio ao médico na identificação das manifestações clínicas; a montagem e a execução do plano de cuidados do paciente; a administração de medicação conforme a prescrição médica e a orientação aos pais.…”
Section: Publicação (P)unclassified